Occurrence of seed infection by Colletotrichum capsici (Syd) butler and bioby in Cowpea grown in Burkina faso: Significance and control by Benlate - Thiram - Séreme, P.; Mathur, S.B. (Copenhagen (Dinamarca), 1996)
Sumarios (En, Fr)
13 ref.
Keywords: COLLETOTRICHUM CAPSICI; ENFERMEDADES INFECCIOSAS; INFECCION; SEMILLAS; CONTROL DE ENFERMEDADES